Guiana Francesa: uma análise geohistórica - Geraldine Rosas Duarte (Confins, 2016)
This article aims to reflect on the geohistorical characteristics of French Guiana, addressing its physical, demographic and structural features. The analysis provides an overview of the internal characteristics of the overseas territory, enabling a deeper reflection on its regional integration.